Tagua Powder as a Bio-Based Filler for Waterborne Acrylic Coatings: Enhancing Performances and Sustainability - Andrea Cristoforetti; Luca Donati; Stefano Rossi (Surfaces)
The increasing demand for sustainable materials in the coatings industry is driving the replacement of synthetic components with bio-based alternatives. In this study, Tagua powder, derived from the seeds of Phytelephas macrocarpa, was incorporated as a filler in a waterborne acrylic-based coating to evaluate its effects on abrasion and protective properties. Two different particle size ranges (40–63 µm and ≤40 µm) and concentrations (1 wt% and 3 wt%) were tested. Morphological analyses confirmed a homogeneous dispersion of the filler within the coating matrix, with larger particles inducing surface roughness. The results demonstrated that the addition of Tagua powder significantly improved abrasion resistance, with the coating containing 3 wt% of larger particles (40–63 µm), reducing mass loss by 24.5% after 1000 Taber abrasion cycles compared to the reference coating. However, due to its lignocellulosic nature, the filler increased water uptake, leading to a decrease in barrier properties. Coatings with 3 wt% filler exhibited a reduction in electrochemical impedance modulus by approximately one order of magnitude after 670 h of immersion in a 3.5 wt% NaCl solution, indicating lower corrosion protection. Despite this, the performance in filiform corrosion resistance remained comparable to the reference, suggesting that Tagua powder does not critically affect adhesion properties. These findings highlight the potential of Tagua powder as a functional bio-based filler, offering enhanced mechanical durability while requiring a strategic coating design, such as a multilayer system, to mitigate moisture sensitivity. This study provides valuable insights into the development of environmentally friendly coatings with improved wear resistance.